The Impact of Social Networking Sites on the Social Relations of University Youth: An applied study on University of Sharjah students in the United Arab Emirates - Alketbi, Aisha Ali; Noufal, Zezit Mostafa (Al-Adab Journal, 2023)
The current study seeks to achieve the main objective, which is the impact of social networking sites on the social relations of university youth at the University of Sharjah, from which emerged the sub-objectives: to reveal the motives of the youth of the University of Sharjah to social networking sites in their daily lives, and to determine the impact of social networking sites on the personality of university youth Sharjah and their behaviors, and the relations of the University of Sharjah youth with their families, friends and relatives. The study was applied to the youth of the University of Sharjah in the United Arab Emirates, in the academic year 2021-2022, for the second semester. The study relied on the sample social survey method, and the study sample amounted to (1823) individuals. The study found the following results: that the highest use and preference for social media platforms came in three platforms: Facebook, WhatsApp, and Instagram, and that the number of hours university youth spend using social media platforms and sites is between (4 to 6 hours) per day. And that social networking sites affect the personality and behavior of university youth through the contents of fashion and entertainment, and the impact of social networking sites on the relationship of university youth with their families, with quick anger when a family member interrupts them. The study recommends allocating smart places to support youth initiatives and encourage them to create different websites on the Internet and support them instead of entertainment and entertainment, and to establish electronic educational centers and platforms to adopt youth ideas, which work to build capacities and raise competencies and share them with the government work of the UAE to present such innovative ideas through Social networking sites via the Internet.